Stabilization of parameters of cupola melting - L. E. Rovin; S. L. Rovin (Литьë и металлургия)
Main disadvantages of cupola melting at the domestic enterprises is instability of the process and, as a result, unstable, quality of the manufactured cast iron. The article examines ways to solve this problem by implementing automatic systems and control of wind parameters, temperature of affluent gases and hot metal, as well as level of furnace feed.